From crystalline to amorphous calcium pyrophosphates: A solid state Nuclear Magnetic Resonance perspective. (February 2016) - Gras, Pierre; Baker, Annabelle; Combes, Christèle; Rey, Christian; Sarda, Stéphanie; Wright, Adrian J.; Smith, Mark E.; Hanna, John V.; Gervais, Christel; Laurencin, Danielle; Bonhomme, Christian
Graphical abstract: Abstract: Hydrated calcium pyrophosphates (CPP, Ca2 P2 O7 ·nH2 O) are a fundamental family of materials among osteoarticular pathologic calcifications. In this contribution, a comprehensive multinuclear NMR (Nuclear Magnetic Resonance) study of four crystalline and two amorphous phases of this family is presented. 1 H, 31 P and 43 Ca MAS (Magic Angle Spinning) NMR spectra were recorded, leading to informative fingerprints characterizing each compound. In particular, different 1 H and 43 Ca solid state NMR signatures were observed for the amorphous phases, depending on the synthetic procedure used. The NMR parameters of the crystalline phases were determined using the GIPAW (Gauge Including Projected Augmented Wave) DFT approach, based on first-principles calculations. In some cases, relaxed structures were found to improve the agreement between experimental and calculated values, demonstrating the importance of proton positions and pyrophosphate local geometry in this particular NMR crystallography approach. Such calculations serve as a basis for the future ab initio modeling of the amorphous CPP phases. Statement of significance: The general concept of NMR crystallography is applied to the detailed study of calcium pyrophosphates (CPP), whether hydrated or not, and whether crystalline or amorphous. CPP are a fundamental family of materials among osteoarticular pathologic calcifications. Their prevalence increases with age, impacting on 17.5% of the population after the age of 80. They are frequently involved or associated with acute articular arthritis such as pseudogout. Current treatments are mainly directed at relieving the symptoms of joint inflammation but not at inhibiting CPP formation nor at dissolving these crystals. The combination of advanced NMR techniques, modeling and DFT based calculation of NMR parameters allows new original insights in the detailed structural description of this important class of biomaterials.